Entre letra e imagen: el cine intersticial de Gustavo Fontán - Eduardo A. Russo (Cuadernos LIRICO)
The work of Gustavo Fontán fits notably into the figure of the filmaker-writer. His extensive production has encompassed various forms of writing and filmmaking. But it is during the last few years, by deepening the essayistic angle of an intermedia territory, that his itinerary has displayed renewed relationships between his writings and films. His book El lago helado (written with Gloria Peirano, 2018) was elaborated in closed relation with his video trilogy of the same name. Maraña (2021) dialogues with his “cycle of the river” films and the documentary El piso del viento (2021) in addicion to extending far-reaching lines in his poetics. In turn, the writings in his volume Del natural (2022) paved the way for the first two films of a tetralogy the he made during the pandemic. These texts by Fontán participate in the forms of filming diary, the notebook and the reflective essay, without sticking to any usual category. Even fewer stick to the instrumental functions that link the film script with the mise-en-scène, but rather the work between the letter and the line, between contemplation, reading and writing. As modes of questioning about looking at and listening to the world, about the possibility of seeing images grow, of assisting them in their emergence rather than constructing them, Fontán’s films and books are a key example of a work cultivated in the interstices, in the glimpse and the interhearing, between the page and the screen.